2010
DOI: 10.3928/01477447-20100924-04
|View full text |Cite
|
Sign up to set email alerts
|

Digital Templating in Primary Total Hip and Knee Arthroplasty

Abstract: The use of digital radiography is becoming more prevalent in orthopedics. This transition impacts the ability to preoperatively plan for implants in total hip arthroplasty (THA) and total knee arthroplasty (TKA). This article reports on the clinical success of digital templating using the Advanced Case Plan (Stryker Imaging, Flower Mound, Texas) system in primary THA and TKA. Digital radiographs of 269 consecutive patients undergoing primary THA (93 cases) or TKA (176 cases) were templated using the Advanced C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 12 publications
1
58
0
Order By: Relevance
“…15 These results are comparable to previous findings by the current authors that digital templating accurately predicted tibial size in 63% and femoral size in 69% of 176 consecutive TKAs. 4 Results from the current study showed a significant improvement in templating accuracy to 90% for tibial and 83% for femoral component sizes. Increased experience with digital templating by the senior author was likely the cause for the improved templating accuracy.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…15 These results are comparable to previous findings by the current authors that digital templating accurately predicted tibial size in 63% and femoral size in 69% of 176 consecutive TKAs. 4 Results from the current study showed a significant improvement in templating accuracy to 90% for tibial and 83% for femoral component sizes. Increased experience with digital templating by the senior author was likely the cause for the improved templating accuracy.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, as TDI continues to be refined and integrated in hospital systems, less instrumentation could help improve tray and operating room turnover to allow for more cases to be completed, minimize surface area for contamination, and lower hospital costs per procedure. 4 Inventory control by vendors using scheduling software to control inventory more tightly could improve operating room efficiency and reduce manufacturing costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardization of the acquisition of radiographic images is essential for accurate measurement of distances and their biomechanical interpretation (Levine et al 2010). While the most common calibration method is based on an extracorporeal metallic sphere with a defined diameter positioned at the supposed vertical height of the center of the hip, intracorporeal implants have also been used successfully (Meyer and Kotecha 2008, Paul et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The inclination angle was defined as the angle between the line joining the inferior teardrop points and the axis of the opening of the acetabular component. Acetabular anteversion was measured with computer software (Advanced CasePlan Digital Templating Planning Software, Stryker Orthopedics, Mahwah, NJ) [14]. The mean inclination angle of the cup was 44° (23–70°), and the mean anteversion angle was 14° (4–25°).…”
Section: Methodsmentioning
confidence: 99%